Revalidation of the ATTRACTION-4 study in a real-world setting: a multicenter, retrospective propensity score matching study in China - Dai, Yuhong; Liu, Yongqing; Gong, Zhimin; He, Lilin; Wang, Lei; Yang, Wenjie; Qiu, Ping; Zhang, Fangyuan; Yuan, Xianglin; Cheng, Henghui; Qiu, Hong (Frontiers in Immunology, 2023)
Background Immune-checkpoint inhibitors (ICIs) combined with chemotherapy have been successfully used in clinical trials to treat advanced gastric cancer. However, the efficacy and safety of first-line immunotherapy combined with chemotherapy in Chinese patients are unknown. Methods This multicenter retrospective study included patients with human epidermal growth factor receptor-2 (HER-2) negative advanced gastric cancer treated with first-line chemotherapy or chemotherapy with an ICI between January 2019 and December 2022. Propensity score matching was used to compare progression-free survival (PFS), overall survival, objective response rates, and adverse reactions between cohorts. Results After propensity score matching, 138 patients, who had balanced baseline characteristics, were included in the chemotherapy and combination treatment groups. The median follow-up duration was 16.90 months, and the median PFS was 8.53 months (95% confidence interval [CI] 7.77-9.28) in the combination treatment group and 5.97 months (95% CI 4.56-7.37) in the chemotherapy group. The median survival duration was 17.05 months (95% CI 14.18-19.92) in the combination treatment group and 16.46 months (95% CI 12.99-19.93) in the chemotherapy group. The PFS subgroup analysis revealed that age ≥65 years, women, Eastern Cooperative Oncology Group performance status of 1, non-signet ring cell carcinoma, esophagogastric junction, liver metastasis, peritoneal metastasis, no massive ascites, only one metastatic organ, and combined platinum-based chemotherapy correlated with treatment benefit. The incidences of adverse events above grade 3 were comparable between groups. Conclusions Our study confirmed the ATTRACTION-4 trial results. Compared with chemotherapy, first-line ICIs combined with chemotherapy prolonged PFS but did not improve overall survival in patients with HER-2-negative advanced gastric cancer.